Renewable Sources and their Applications in Biotechnological Processes - Mascarenhas Santos, Maria do Socorro; Batistote, Margareth (Fronteira: Journal of Social, Technological and Environmental Science, 2020)
Brazil has edaphoclimatic conditions to produce a diversity of crops with energetic potential. Thus, the study aims to correlate the technological parameters of biomasses suitable for fermentation, quantify metabolites produced by yeast FT-858, as well as assess the yield and fermentative efficiency for bioethanol production. It was performed studies of technological qualities of the biomasses and fermentative capacity test. For metabolites production, the yeast FT-858 was pre-grown in liquid medium (YPD 2%), recovered and inoculated in the substrates, and aliquots were collected for analysis of ethanol concentration by gas chromatography and glycerol accumulation by enzymatic kit of triglycerides. The yield and fermentative efficiency were assessed by consumption of sugar using DNS method, and ethanol density using digital densimeter. According to the results, the yeast presented better performance in saccharine sorghum, which also presented more expressive values of fermentative efficiency and yield. Saccharine sorghum has great bioenergetic potential and can be used as complement to sugarcane to increase ethanol production.